2016
DOI: 10.1007/s12603-016-0684-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional characterization of pre-frailty among elderly patients consulting primary care centres

Abstract: Pre-frailty is very common among elderly subjects consulting primary care centres. Weakness, slowness, diabetes, pain and polypharmacy should alert healthcare professionals to the onset of a frailty process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…The fact that the women in our study showed an increased risk of frailty in the bivariate analysis corroborates results from other studies reporting a higher prevalence of frailty in women in cross-sectional studies [2,18]. However, this effect disappeared when adjusted for other variables such as arthritis, depression, number of medications, physical activity, abdominal obesity and certain blood biomarkers, thereby undermining a genuine female-sex effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that the women in our study showed an increased risk of frailty in the bivariate analysis corroborates results from other studies reporting a higher prevalence of frailty in women in cross-sectional studies [2,18]. However, this effect disappeared when adjusted for other variables such as arthritis, depression, number of medications, physical activity, abdominal obesity and certain blood biomarkers, thereby undermining a genuine female-sex effect.…”
Section: Discussionsupporting
confidence: 89%
“…We interpret the effect of arthritis to be a consequence of limited physical activity secondary to pain, a highly prevalent clinical condition in the elderly population [18] and a possible trigger of the frailty process. Depression has been reported elsewhere as a contributor to frailty [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in relation to the movement patterns, in our study the frail and pre-frail clearly showed the opposite profile of movement behaviors compared to robust older people, both in the whole sample and also in relation to each sex, spending more time in SB and less in LPA and MVPA than the entire sample, similarly to other previously published studies [30,45,46]. Consequently, older men and women seem to follow similar patterns related to PA and SB, even though the effect of these movement behaviors on bone health differs according to sex and frailty status.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of arthritis and musculoskeletal diseases, which are more frequent in older women because of menopause-related osteoporosis, is possibly due to limited physical activity secondary to pain. A high prevalence of pain in elderly subjects and its relationship with arthritis and weakness has been reported elsewhere [25,26]. Pain may lead to low physical activity and immobility, and, consequently, to muscle atrophy and loss of muscle strength.…”
Section: Citationmentioning
confidence: 95%